Analisa Pemanfaatan, Tantangan dan Opportunie Cloud ERP di Indonesia - syarifah farrah (PT Triputra Sejahtera Prima, 2023)
The development of ERP in Indonesia has a close relationship with PT. Astra International. The development of technology began in the 2000s when the internet was growing rapidly. By using a qualitative descriptive method, the authors try to analyze the benefits, challenges and opportunities of Cloud ERP in Indonesia. Where this research method has the aim of describing an object of research through samples or data that has been collected and making general conclusions. Based on a report released by markets and markets, it is projected that cloud computing will experience growth at a CAGR of 17.9% with an estimated USD 1,250.9 billion in 2027 from an estimated USD 545.8 billion in 2022. Cloud ERP is a breakthrough for a new delivery model in ERP systems. Where Cloud ERP is growing rapidly around the world, because it is felt to be able to provide organizations with a variety of new characteristics such as advantages in business competition and low costs. Based on data from a dissertation on Cloud ERP in the context of micro, small and medium enterprises (SMEs) in Indonesia, it shows that in 2012 the composition of the national gross domestic product (GDP) was composed of 58.1% of SMEs, 41.9% of large businesses. where all SMEs contributed to employment absorption of 97.2%. For this reason, the use of Cloud ERP is very important for SMEs so that SMEs are still able to run their business and be able to compete with large companies. Based on the analysis carried out, it can be concluded that Cloud Computing allows a company to apply and adopt innovative technologies such as Cloud ERP. The reliability of the infrastructure owned by Cloud ERP because it utilizes the internet is considered to have been economically successful and able to replace traditional ERP functions.